VD_FINDINFO Décision / 2014 / 139 vom 24. Januar 2014 - VD Tribunal cantonal (2014)
CLASSEMENT DE LA PROCÉDURE, FRAIS DE LA PROCÉDURE | 52 CP, 393 al. 1 let. a CPP (CH), 395 let. b CPP (CH), 426 al. 2 CPP (CH)